KENDALA-KENDALA DALAM PEMBELAJARAN PAI DI SMK SWASTA SIDOARJO - Rahma Azizah; Budi Haryanto (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to identify the obstacles faced by teachers in teaching Islamic Religious Education (IRE) and the factors that cause students' indifference towards IRE lessons at SMK Anugrah Ilmu Sidoarjo. This study uses a descriptive qualitative approach with a phenomenological method. Data in this study were obtained through observation and interviews. The research informants consisted of an Islamic Religious Education teacher and several 11th grade students who were selected based on the teacher's recommendations and showed a prominent attitude towards Islamic Religious Education learning. Observations were conducted non-participatively to obtain a natural picture of the learning process, while data analysis was carried out based on the model proposed by Miles, Huberman, and Saldana, which includes data processing, information presentation, and conclusion drawing, and was tested using triangulation techniques to ensure its validity. This study found that obstacles in PAI learning come from various aspects, such as limited time for the learning process, teaching methods that lack variety, low use of learning media, low student motivation, and the influence of family and social environments. One important finding from this study is that vocational school students consider vocational subjects to be more important than PAI because they are considered more relevant to the needs of the world of work, making PAI an additional subject that receives less attention. This situation has an impact on the low level of student involvement and concern in the PAI learning process. This view is also influenced by the background of the students and their families, many of whom come from secular backgrounds or are not devout in their worship, while others come from communities with moderate levels of Islamic values, so that religious values are not yet a priority in their daily lives.